Development of an Automated Indoor Plant with IoT System - Khalid, Irham; Yaacob, Megat Satria Zainuddin (Progress in Engineering Application and Technology, 2023)
The purpose of this research is to demonstrate an automatic system for taking care of plant indoor. This study aims to design a system that can monitor real time condition of plant parameter with IoT based technology. The system is develop using sensor and actuator with application used. The system determined the best situation of soil, temperature, and light for the indoor plant environment. This idea offers an automated system to take care if indoor plant and can be improved by doing a big scale for greenhouse using automated system.